Tiny pretty things / 1 - Charaipotra, Sona (Tiny pretty things, 2015)
Gigi, Bette, and June, three top students at an exclusive Manhattan ballet school, have seen their fair share of drama. Free-spirited new girl Gigi just wants to dance -- but the very act might kill her. Privileged New Yorker Bette's desire to escape the shadow of her ballet star sister brings out a dangerous edge in her. And perfectionist June needs to land a lead role this year or her controlling mother will put an end to her dancing dreams forever. When every dancer is both friend and foe, the girls will sacrifice, manipulate, and backstab to be the best of the best.